Which of the following correctly demonstrates the Associative Property of Addition?

A. m*(x*y)=(m*x)*y
B. y-(x+1)=(y-x)+1
C. x*(y+z)=(x+y)+z
D. (x+y)+z+r=x+(y+z)+r

1 answer

The Associative Property of Addition states that when adding three or more numbers, the way in which the numbers are grouped does not change their sum.

Among the options given:

A. \( m*(xy)=(mx)*y \) - This demonstrates the Associative Property of Multiplication, not Addition.

B. \( y-(x+1)=(y-x)+1 \) - This is not related to the Associative Property of Addition.

C. \( x*(y+z)=(x+y)+z \) - This demonstrates the Associative Property of Multiplication, not Addition.

D. \( (x+y)+z+r=x+(y+z)+r \) - This correctly demonstrates the Associative Property of Addition. It shows that whether you group \( (x+y) \) or \( (y+z) \), you still get the same result when adding all the elements.

Thus, the correct answer is:

D. \( (x+y)+z+r=x+(y+z)+r \)